The case for a framework agreement on investment - Gary Hufbauer; Sherry Stephenson (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
Looking at a rear-view mirror, skeptics assert that efforts to create a plurilateral Investment Framework Agreement (IFA) are doomed. We argue that conditions on the ground have changed: in the 2010s, unlike the 1990s, many countries would welcome an IFA under WTO auspices.
Keywords: 330